2008
DOI: 10.1103/physrevb.78.104402
|View full text |Cite
|
Sign up to set email alerts
|

Exchange interactions and critical temperature of bulk and thin films of MnSi: A density functional theory study

Abstract: Recent theoretical work [H. Wu et al., Phys. Rev. Lett. 92, 237202 (2004); M. Hortamani et al., Phys. Rev. B 74, 205305 (2006); M. Hortamani, Ph.D. thesis, Freie Universität, Berlin, 2006] predicted ferromagnetism at zero temperature in thin MnSi films of B2-type crystal structure on Si(100). The relevance of this finding for finite-temperature experiments needs to be clarified by further investigations, since bulk MnSi is a weak ferromagnet with an experimentally measured Curie temperature of only Tc Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 29 publications
(34 reference statements)
2
38
0
1
Order By: Relevance
“…Exchange interactions in bulk and thin films of MnSi were studied in order to explain the ferromagnetism observed in thin films of MnSi/Si(100) [15]. Hopkinson et al considered the electrons in the magnetic ground state of MnSi to be of dual character [16]; leading to both the local moment and itinerant conduction electrons that mediate the magnetic interaction through RKKY type interaction [17].…”
Section: Introductionmentioning
confidence: 99%
“…Exchange interactions in bulk and thin films of MnSi were studied in order to explain the ferromagnetism observed in thin films of MnSi/Si(100) [15]. Hopkinson et al considered the electrons in the magnetic ground state of MnSi to be of dual character [16]; leading to both the local moment and itinerant conduction electrons that mediate the magnetic interaction through RKKY type interaction [17].…”
Section: Introductionmentioning
confidence: 99%
“…For thin films MnSi/Si(001), a similar DFT study has been reported recently. 48 However, structurally, electronically, and magnetically the δ-doped Si/Mn heterostructures differ considerably from MnSi/Si(001) thin films.…”
Section: Introductionmentioning
confidence: 99%
“…2,11 This order is explained by the formation of c-MnSi phase with B2-like (CsCl) crystal structure stabilized with tetragonal distortion due to favorable lattice mismatch between the film and substrate. 1 Recently we reported the HT FM appearance with T C ≈ 330 K in 70 nm thick Mn x Si 1-x (x ≈ 0.52-0.55) films grown on the Al 2 O 3 (0001) substrates by pulsed laser deposition (PLD) technique. 3,4 We argued that the observed HT FM has a defect-induced nature: it is due to formation of local magnetic moments on the Si vacancies inside the MnSi matrix and the strong exchange coupling between these moments mediated by spin fluctuations of itinerant carriers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The perfect single crystal ε-MnSi with B20-type of structure possesses at low temperatures (≤ 30 K) intriguing magnetic and transport phenomena caused by formation of new magnetic quasiparticles -skyrmions (see Ref. 6 and references therein).…”
Section: Introductionmentioning
confidence: 99%